2003
DOI: 10.1046/j.1365-2249.2003.02159.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of p53 in the immunobiology of cutaneous squamous cell carcinoma

Abstract: SUMMARYCutaneous squamous cell carcinoma is typically characterized by the over-expression of the tumour suppressor protein p53. Considerable evidence suggests that immune competence is important in the control of cutaneous SCC. We discuss the immunobiology of p53 and its relevance to cutaneous SCC, including the potential interaction with human papillomavirus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 80 publications
(85 reference statements)
0
23
1
Order By: Relevance
“…Insights into the molecular pathogenesis of cutaneous SCC are slowly emerging (17,40,41). Previous studies have shown that loss of nuclear factor nB (NF-nB) activity, through enhanced InB expression, or depletion of SMAD4 in murine skin confers susceptibility to SCC, in part, through promotion of unbalanced keratinocyte proliferation (41)(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Insights into the molecular pathogenesis of cutaneous SCC are slowly emerging (17,40,41). Previous studies have shown that loss of nuclear factor nB (NF-nB) activity, through enhanced InB expression, or depletion of SMAD4 in murine skin confers susceptibility to SCC, in part, through promotion of unbalanced keratinocyte proliferation (41)(42)(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…The viruses considered to be of high oncogenic potential include HPVs 16,18,31,33,35,39,45,51,55,56,58,59, 66 and 68 (5), and these have been associated with the development of various types of human neoplasias, particularly lesions of epithelial cells of the uterine cervix, urethra, anogenital region, skin, digestive tract, tracheal/bronchial and nasal mucosa and oral mucosa (6,7). DNA sequences of HPV 16 and 18 are found in approximately 85% of invasive squamous cell carcinomas and their precursors, such as grave dysplasia and carcinoma in situ.…”
Section: Introductionmentioning
confidence: 99%
“…Research into immune response to p53 had led to promising therapeutic potential. p53-specific cytotoxic T lymphocytes capable of mediating protective immunity to tumours have been generated in murine models (Black et al, 2003,Clin Exp Immunol.). Adoptive transfer of p53 specific cytotoxic T lymphocytes generated in p53-/-mice confers immunity on the recipient to p53 overexpressing murine tumour (Vierboom et al, 1997,J Exp Med.).…”
Section: Conclusion/ Future Directionsmentioning
confidence: 99%
“…Following viral genome integration, E6 and E7 oncoproteins are overexpressed, with inhibition of apoptosis via p53 dependent and independent mechanisms (Thomas et al, 1999, Oncogene). E6 protein from the cervical associated HPC-16 mediates degradation of p53 (Black et al, 2003,Clin Exp Immunol). A common p53 polymorphism at position 72 replacing proline with arginine renders p53 more susceptible to E6 mediated degradation.…”
Section: Human Papilloma Virusmentioning
confidence: 99%
See 1 more Smart Citation